Exploring Higher Education Students' Perspective of Using Padlet as a Tool for Developing Writing Skill - Bayu Imam Cahyono; Tiara Asa Pertiwi; Taufik Arochman (International Journal of English Linguistics, Literature, and Education (IJELLE), 2024)
This research aims to explore the use of Padlet to enhance writing skills among university students. To achieve this, the authors use qualitative research involving questionnaires and interviews with 6th-semester English Education students at Universitas Tidar. For data analysis, the authors briefly make interpretations and conclusions based on the answers from the questionnaire and interviews. The findings reveal that Padlet facilitates improved writing by enabling real-time feedback and peer interaction. Students reported better organization and creativity in their writing tasks. Students also found Padlet to be enjoyable to use, with many interactive features that enhance the writing experience. Despite some challenges with its basic writing format, Padlet proved effective for non-academic writing. However, its efficacy for academic writing requires further investigation.